Sogno e delirio: breve excursus nella storia della psichiatria - Fargnoli, Domenico (Il sogno della farfalla, 2020)
In the history of psychiatry a similarity between dreams and delusions has often been recognized. According to widespread beliefs of the Western culture, delusions would not only find their roots in oniric images but would also share the same thought and language formal aspects. The author retraces the most important theories that from the 18th and 19th century until nowadays have established an analogy between these two dimensions. Eventually the article analyses the most recent Human Birth Theory by Massimo Fagioli. Through an original definition of the pulsion and the oniric image, this theory radically criticizes the famous Spinozan idea which affirmed an equivalence between dreams and delusions.